Role of early tracheostomy for preventing ventilator associated pneumonia in intensive care unit: a review - Swain, Santosh Kumar; Jena, Pragnya Paramita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Tracheostomy often plays a crucial role in airway management of the patients in intensive critical unit (ICU). Tracheostomy is often helpful for improvement of the respiratory mechanics and the patient comfort. There are several advantages of the trachesotomy over the endotracheal tube intubation such as avoidance of the injury of the larynx, provide a stable airway, facilitates pulmonary toilet and facilitates ventilation. It has been suggested that tracheostomy also helpful to reduce the risk of ventilator associated pneumonia (VAP) in comparison to the trans-laryngeal intubation. VAP is a type of nosocomial infection which has been associated with presence of mechanical ventilation. Despite significant improvement in managing the intubated patients, VAP remains a common and sometimes fatal complication in the ICU. Clinician’s attitude towards trachesotomy may be still heterogeneous in ICU and the decision for performing tracheostomy is still challenging. However, early tracheostomy is associated with less VAP, less ICU stay, avoid higher number of intubation in early group of tracheostomy and higher patient comfort. The purpose of this review article was to discuss the etiopathology of VAP, epidemiology, role of early tracheostomy in VAP and prevention of the VAP in patients with mechanical ventilation in ICU.